Guidelines for the Development of Comprehensive Care Centers for Congenital Adrenal Hyperplasia: Guidance from the CARES Foundation Initiative. (11th November 2010) - Auchus, Richard J.; Witchel, Selma Feldman; Leight, Kelly R.; Aisenberg, Javier; Azziz, Ricardo; Bachega, Tânia A.; Baker, Linda A.; Baratz, Arlene B.; Baskin, Laurence S.; Berenbaum, Sheri A.; Breault, David T.; Cerame, Barbara I.; et al.
Abstract : Patients with rare and complex diseases such as congenital adrenal hyperplasia (CAH) often receive fragmented and inadequate care unless efforts are coordinated among providers. Translating the concepts of the medical home and comprehensive health care for individuals with CAH offers many benefits for the affected individuals and their families. This manuscript represents the recommendations of a 1.5 day meeting held in September 2009 to discuss the ideal goals for comprehensive care centers for newborns, infants, children, adolescents, and adults with CAH. Participants included pediatric endocrinologists, internal medicine and reproductive endocrinologists, pediatric urologists, pediatric surgeons, psychologists, and pediatric endocrine nurse educators. One unique aspect of this meeting was the active participation of individuals personally affected by CAH as patients or parents of patients. Representatives of Health Research and Services Administration (HRSA), New York-Mid-Atlantic Consortium for Genetics and Newborn Screening Services (NYMAC), and National Newborn Screening and Genetics Resource Center (NNSGRC) also participated. Thus, this document should serve as a "roadmap" for the development phases of comprehensive care centers (CCC) for individuals and families affected by CAH.